How does the “Global South” mobilize resources for environmental projects - Renato Machado (Revista Conjuntura Austral)
This paper analyzes how the different regions and countries of the (conceptually subjective) “Global South” mobilized resources for environmental projects, that were partially sponsored by the Global Environment Facility (GEF). The quantitative analyses were mostly based on per capita indicators, which form the foundation for most of the conclusions presented. The data analysis looked at the information of over 5.000 GEF projects- amounting to more than US$ 160 billion, including cofinance- ever since its establishment in the early 1990s, until the first semester of 2023. The main findings suggest that smaller countries, especially those composed of low-lying islands, present the best per capita ratios of resources mobilized (GEF grants plus cofinance) for the projects. Size, necessity and GEF’s inclusive, but finite, resources, seem to catalyze these results. Among the three “macro” regions examined, Latin America and the Caribbean (LAC) presents the best resources mobilized per capita ratios, and parts of Asia and the Pacific (ASIAPAC) excel at completing existing projects. One-country projects followed through better than multi-country ones. Finally, this paper concludes that wars and superior political instability are relevant factors that make countries cancel more projects. Theoretical hypotheses that help to corroborate most of these findings are included.